2020
DOI: 10.1002/aws2.1189
|View full text |Cite
|
Sign up to set email alerts
|

How permeable could a reverse osmosis membrane be if it was specifically developed for uncharged organic solute rejection?

Abstract: Here, we present both experimental data and modeling results of the removal of four different polar organic solutes by six different commercial nanofiltration (NF) and reverse osmosis (RO) membranes in a natural groundwater matrix. These results are significant for two reasons. First, three of the polar organic solutes are contaminants commonly found in both drinking water aquifers and municipal wastewaters and, hence, are particularly relevant to the protection of public health in drinking water production an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In contrast to γ LW , γ – of membranes varies greatly for the different polymer chemistries presented in Figure b. PANi (polyaniline) and PAN membranes, which are highly hydrophilic and fouling-resistant, demonstrate the largest γ – , while poly­(vinyl chloride) (PVC), polysulfone (PSf), and polypropylene (PP) are more hydrophobic materials with lower γ – values. The Lewis acid–base nature of each material is a function of its charged functional groups and moieties possessing unpaired electrons (e.g., R-Ö-R, R- N⃛ -R, etc.)…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to γ LW , γ – of membranes varies greatly for the different polymer chemistries presented in Figure b. PANi (polyaniline) and PAN membranes, which are highly hydrophilic and fouling-resistant, demonstrate the largest γ – , while poly­(vinyl chloride) (PVC), polysulfone (PSf), and polypropylene (PP) are more hydrophobic materials with lower γ – values. The Lewis acid–base nature of each material is a function of its charged functional groups and moieties possessing unpaired electrons (e.g., R-Ö-R, R- N⃛ -R, etc.)…”
Section: Discussionmentioning
confidence: 98%
“…Thus, previous studies have suggested that the size, porosity, thickness, and thermodynamic partitioning coefficient of membranes are all required to accurately predict the transport of such contaminants through RO membranes. 117 Additionally, water clustering can alter the energy of diffusion due to strong intermolecular bonding and the ability of water to be both a double donor and acceptor of hydrogen bonds. 118 Water clusters take the shape that maximizes the number of hydrogen bonds and minimizes geometrical strain.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction of small neutral solute rejection with RO membranes remains challenging because there is no universal indicator that correlates with the permselectivity of these contaminants. Thus, previous studies have suggested that the size, porosity, thickness, and thermodynamic partitioning coefficient of membranes are all required to accurately predict the transport of such contaminants through RO membranes …”
Section: Discussionmentioning
confidence: 99%
“… 78 A great deal of research concerns the creation of “fit-for-purpose” NF membranes, 79 which are modified structurally and/or chemically to provide precise solute separation at the subnanometer or subangstrom scale (e.g., the passage of Ca 2+ ions to minimize remineralization needs and scaling propensity while retaining PFAS). 80 Still, some small, polar KUECs, such as 1,4-dioxane and NDMA, can pass through many types of NF and RO membranes (e.g., NDMA removals vary from ∼5–10% with NF to ∼90% with seawater RO), 81 , 82 underscoring the value of multibarrier approaches.…”
Section: Reducing Uncertainties In Drinking Water Using the “Minus Ap...mentioning
confidence: 99%